Design of experiment (DoE)-based formulation design of bepotastine sustained-release tablet and in vitro-in vivo pharmacokinetic correlation - Jeon, Sang Won; Park, Jin Hyun; Kim, Joo Eun; Park, Young Joon (Journal of Pharmaceutical Investigation, 2023)
Purpose: Bepotastine besilate, a second-generation antihistamine commonly prescribed to treat allergic rhinitis and urticarial/pruritus, has a short half-life (t1/2) and is currently available as an immediate-release tablet, administered twice daily. The development of a sustained-release bepotastine formulation remains limited. Methods: An experimental method was used to develop a sustained-release bepotastine tablet that can be taken once daily. The formulated sustained-release bepotastine tablet was biologically equivalent to the commercially available Talion® taken twice daily. Considering the target formulation characteristics, the in vitro dissolution rates at 1, 3, and 10 h were predicted as critical quality attributes, taking into account the dissolution and bioequivalence profile of Talion®. Results: Factors capable of critically impacting the sustained-release pattern were selected by performing a screening study; the X value, which affects the Y value (1, 3, and 10 h dissolution rates), was identified using hydroxypropyl methylcellulose, polyvinyl-alcohol, and citric acid. For the three identified independent variables, a design space was derived using the extreme vertices design from among the experimental design mixture methods, optimized within the X values of the derived design space. The optimized formulation employed a direct compression process to minimize time and cost. The dissolution rates at 1, 3, and 10 h were 24.9, 47.4, and 88.8%, respectively, exhibiting an appropriate dissolution profile to induce sustained-release effects in the human body. Conclusion: Bepotastine sustained-release tablet, which can be administered once daily, developed by applying the design of experiment method, was biologically equivalent to the Talion® tablet, which is administered twice daily. Therefore, the developed sustained-release technology using two or more hydrophilic polymers can be applied to various pharmaceuticals in the future as a platform to overcome the technical and commercial limitations of sustained-release agents.
Keywords: Bepotastine besilate; Design of experiment; Extreme vertices design; Pharmacokinetic profile; Sustained-release; Taken once a day